Impact of repetitive DNA on sex chromosome evolution in plants - Hobza, Roman; Kubat, Zdenek; Cegan, Radim; Jesionek, Wojciech; Vyskot, Boris; Kejnovsky, Eduard (Chromosome research, 2015)
Structurally and functionally diverged sex chromosomes have evolved in many animals as well as in some plants. Sex chromosomes represent a specific genomic region(s) with locally suppressed recombination. As a consequence, repetitive sequences involving transposable elements, tandem repeats (satellites and microsatellites), and organellar DNA accumulate on the Y (W) chromosomes. In this paper, we review the main types of repetitive elements, their gathering on the Y chromosome, and discuss new findings showing that not only accumulation of various repeats in non-recombining regions but also opposite processes form Y chromosome. The aim of this review is also to discuss the mechanisms of repetitive DNA spread involving (retro) transposition, DNA polymerase slippage or unequal crossing-over, as well as modes of repeat removal by ectopic recombination. The intensity of these processes differs in non-recombining region(s) of sex chromosomes when compared to the recombining parts of genome. We also speculate about the relationship between heterochromatinization and the formation of heteromorphic sex chromosomes.
Keywords: molekulární evoluce; chromozomy rostlin; rostliny; pohlavní chromozomy; Chromosomes, Plant; Evolution, Molecular; Gene Expression Regulation, Plant; transpozibilní elementy DNA; repetitivní sekvence nukleových kyselin; Sex Chromosomes; DNA rostlinná; regulace genové exprese u rostlin; Repetitive Sequences, Nucleic Acid; Plants; DNA, Plant; DNA Transposable Elements